STUDI MORFOLOGI SERBUK SARI BEBERAPA SPESIES SOLANUM - Chatri, Moralita; Yesti, Yesti (Sainstek : Jurnal Sains dan Teknologi, 2012)
Pollen is the male genitalia of plants. The pollen morphology can vary within a species and between species, so that it can be used as an identification tool. It also has contribution to other disciplines such as Paleobotany, Paleoecology, Palynology, Aeropalinologi, Medical and determination of  honey quality. This study aims to reveal the pollen morphology of some species of Solanum. The Solanum which was studied were Solanum melongena var. serpentinum (purple and white fruit), Solanum melongena var. esculentum (purple and green fruit), Solanum tuberosum, Solanum torvum and Solanum ferox. The design of research is a descriptive study. The method used was asetolisis with 1% safranin staining in 70% alcohol. The characters pollen morphology observed were: units, polarity, symmetry, size, shape, or form surface ornamentation, number and type of aperture. The results showed the unit of single pollen (monads), with isopolar polarity, radial symmetry and size medium. The length of polar axis (P) ranged from 20 to 32.5, while the length of the equatorial diameter (E) ranged from 20 to 37.7, so the form of Solanum pollen can be classified into classes; Oblate, Suboblate and Oblate spheroidal. Aperture found was 3-4 aperture with the aperture found pore located at the equatorial type. In conclusion, several species of Solanum pollen have similarity in terms of units, polarity, symmetry, size and difference in terms of form and quantity of aperture.Key words: pollen, solanum, identification